Tingkat Kebugaran Karyawan Instalasi Rawat Jalan dengan Menggunakan Metode Rockport di Aplikasi SIPGAR Kementerian Kesehatan - Widi Subakti, Eko; Agung Wibowo, Wahyu; Fitriyana, Fina; Arifin As'ad, Syaiful (Yayasan Mandar Indonesia, 2025)
Physical fitness measurement is an effort to determine a person’s physical fitness level and as a basis for determining the programmed physical exercise needed to improve their fitness. Low fitness levels will have an impact on decreasing productivity and work performance. The aim of this study is to determine the fitness level of employees at the Outpatient Installation of dr. Kariadi Central General Hospital, Semarang, using the Rockport method. This research method is Descriptive Research Using an Evaluation Research design. The sampling technique used in this study is Quota Sampling. The results of measuring the fitness level of Outpatient Installation using the Rockport method in the SIPGAR Application of the Ministry of Health are 6.6% very good,13.4% good, 73.4% sufficient, 6.6% less and 0% very less. The fitness level of Outpatient installation employees as much as 73.4% is sufficient.